Enhancing the thermo-mechanical properties of the interface in composite materials based on the polysulfone polymer matrix - Bendahane, Khaled; Alami, Mohamed; Mokaddem, Allel; Belkheir, Mohammed; Rouissat, Mehdi; Doumi, Bendouma (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: The extensive engagement of nanocomposite and biocomposite polymers, reinforced with natural fibers as fillers, possessed the capability to not only augment material properties but also actively tackle challenges within green ecosystems. This versatile application underscored the dual benefits of improved material performance and a proactive commitment to environmental sustainability. The purpose of the present study was to investigate the temperature-induced damage to the fiber-matrix interface in various composite materials.Methods:The study examined carbon/polysulfone, glass/polysulfone, and alfa/polysulfone biocomposite materials. A genetic approach based on the probabilistic formalism of Weibull was employed to model and analyze the interface damage caused by temperature variations.Results:Notably, the alfa/polysulfone biocomposite emerged as a compelling alternative, showcasing minimal environmental impact and cost-effectiveness. Its fiber-matrix interface behavior closely paralleled that of carbon/polysulfone. The results revealed the remarkable resilience of the carbon/polysulfone composite’s fiber-matrix interface to temperature impacts, distinguishing it from its counterparts.Conclusions: This nuanced understanding provided valuable insights into the distinct responses of composite materials to temperature variations. It also underscored the advantageous characteristics of the alfa/polysulfone biocomposite, positioning it as a sustainable and efficient option in the field of reinforced polymers for modern applications.
Keywords: Polysulfone; Carbon; Alfa; Glass; Temperature; Damage